Photosynthesis Is Widely Distributed among Proteobacteria as Demonstrated by the Phylogeny of PufLM Reaction Center Proteins - Imhoff, Johannes F.; Rahn, Tanja; Künzel, Sven; Neulinger, Sven C. (Frontiers in Microbiology, 2018)
Two different photosystems for performing bacteriochlorophyll-mediated photosynthetic energy conversion are employed in different bacterial phyla. Those bacteria employing a photosystem II type of photosynthetic apparatus include the phototrophic purple bacteria (Proteobacteria), Gemmatimonas and Chloroflexus with their photosynthetic relatives. The proteins of the photosynthetic reaction center PufL and PufM are essential components and are common to all bacteria with a type-II photosynthetic apparatus, including the anaerobic as well as the aerobic phototrophic Proteobacteria. Therefore, PufL and PufM proteins and their genes are perfect tools to evaluate the phylogeny of the photosynthetic apparatus and to study the diversity of the bacteria employing this photosystem in nature. Almost complete pufLM gene sequences and the derived protein sequences from 152 type strains and 45 additional strains of phototrophic Proteobacteria employing photosystem II were compared. The results give interesting and comprehensive insights into the phylogeny of the photosynthetic apparatus and clearly define Chromatiales, Rhodobacterales, Sphingomonadales as major groups distinct from other Alphaproteobacteria, from Betaproteobacteria and from Caulobacterales (Brevundimonas subvibrioides). A special relationship exists between the PufLM sequences of those bacteria employing bacteriochlorophyll b instead of bacteriochlorophyll a. A clear phylogenetic association of aerobic phototrophic purple bacteria to anaerobic purple bacteria according to their PufLM sequences is demonstrated indicating multiple evolutionary lines from anaerobic to aerobic phototrophic purple bacteria. The impact of pufLM gene sequences for studies on the environmental diversity of phototrophic bacteria is discussed and the possibility of their identification on the species level in environmental samples is pointed out.